PHYSIOLOGICAL AND MOLECULAR CHARACTERISTICS OF Bacillus spp. ISOLATED FROM WARM MINERAL WATERS IN VARNA, BULGARIA AS MODEL SYSTEM FOR ORIGIN OF LIFE - IGNATOV, IGNAT; VALCHEVA, NEDYALKA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
In Bulgaria, there are many mineral water springs with opportunities for research on different bacterial species. The present study aims to investigate the bacterial research of mineral waters in the region of Varna, Bulgaria. The results showed three species of genus Bacillus isolated from warm mineral waters, Varna, Bulgaria. The colonial and physiological characteristics of the isolated strains are defined. The isolated strains are identified by software processing with mass spectrometry MALDI-TOF MS Versus 16S rRNA Gene. The results obtained from the biochemical and molecular studies indicate that the isolated strains belong to different species of genus Bacillus. In 2010 Ignatov researched hot mineral waters in Bulgaria and conducted comparative spectrum analysis with cactus juice. In the spectrum of cactus juice and the hot mineral water we observed five comparable local extremums (8.95; 9.67; 9.81; 10.47; 11.13 μm), whereas there was only one (9.10 μm) with the sea water. It is therefore justified to suggest that most probably life originated in hot mineral water. Ignatov and Mosin performed analyses with Bacillus subtilis with heavy water for analyses of the initial condition for origin of life in hot mineral water in primary atmosphere. According to their temperature they can be cold (up to 37° С), warm (from 37°C to 60°C) and hot (over 60°C). This is temperature standard in Bulgaria, European Union. In Varna there is place with stromatolites and cyanobacteria in warm mineral waters. This is the purpose the authors to make research of warm waters in Varna as model system for origin of life in warm and hot mineral waters.